2013
DOI: 10.4236/ojas.2013.32014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a rumen protected B vitamin blend substituted for biotin upon milk production and component yield in lactating dairy cows

Abstract: Results from 4 switchback field trials involving 608 cows were combined to assess the effects of a protected B vitamin blend (BVB) vs 10 mg of unprotected biotin upon milk yield (kg), fat %, protein %, fat yield (kg) and protein yield (kg) in primiparous and multiparous cows. Trials consisted of 3 DHIA periods executed in the order control-test-control. Cows from 45 to 300 days in milk (DIM) at the start of the experiment that were available for all 3 periods were included in the analysis. No diet changes othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…It is noteworthy that our findings align with previous research [ 39 , 40 , 41 ], because the essential role of B vitamins in critical metabolic processes such as gluconeogenesis, fatty acid synthesis, and protein synthesis in dairy cows is well-established. Furthermore, the components of INC, specifically active dry yeast and Selenomethionine, may have played pivotal roles in the observed improvements in milk production performance [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is noteworthy that our findings align with previous research [ 39 , 40 , 41 ], because the essential role of B vitamins in critical metabolic processes such as gluconeogenesis, fatty acid synthesis, and protein synthesis in dairy cows is well-established. Furthermore, the components of INC, specifically active dry yeast and Selenomethionine, may have played pivotal roles in the observed improvements in milk production performance [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Because of the novelty of the RPFA evaluated and in the absence of other corroborating information making definitive conclusions regarding the potential efficacy of providing a rumen-protected source of FA or other B vitamins is not currently feasible. Other studies where a rumen-protected source of FA ( Li et al, 2016 ; Wang et al, 2016 ) or a rumen-protected blend of B vitamins have been fed ( Evans and Mair, 2013 ; Kaur et al, 2018 ) have reported positive responses. Previous research as well as the more recent information provided by Deters et al (2021) in addition to the present research would indicate blood levels of both FA and vitamin B 12 may be inadequate at critical times to meet demands for reproduction, lactation, growth, or health in dairy and beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The NRC (2001) calculated an estimate and reported only folic acid and pantothenic acid to be the limiting B vitamins. However, in the recent past, numerous studies have shown an increase in milk production or component yield (or both) when cows are supplemented with vitamin B compounds (Sacadura et al, 2008;Chen et al, 2011;Evans and Mair, 2013). Similarly, a positive effect of supplementation on health has also been reported, especially in early lactation dairy cows (Graulet et al, 2007;Duplessis et al, 2014;Li et al, 2016), which is achieved via improvement in metabolic efficacy.…”
Section: Introductionmentioning
confidence: 99%